Collaborative Governance in Realizing an Inclusive Village for Persons with Disabilities in Sidorejo Village: Collaborative Governance dalam Mewujudkan Desa Inklusif bagi Penyandang Disabilitas di Kalurahan Sidorejo - Andi Syamsul Muarib; Supardal; Ashar Abdillah (Jurnal Pemerintahan dan Politik, 2026)
Purpose: This study aims to fill the gap between previous studies by integrating the Collaborative Governance process in the context of realizing an Inclusive Village for Persons with Disabilities in Sidorejo Village. Methodology: This research used a qualitative approach, collecting data through observation, interviews, and documentation. The analysis process drew on Ansell and Gash's collaborative governance theory, which emphasizes the importance of direct dialogue, building trust, commitment to the process, shared understanding, and interim outcomes. Findings: The research results show that the collaborative governance process in creating an inclusive village for people with disabilities in Sidorejo has been successful, but challenges remain in practice. Despite this, the Sidorejo Village Government's commitment remains strong, with support from a number of relevant actors. Practical Implication: This research is expected to be a consideration for the Sidorejo village government and related actors in carrying out cross-sector collaboration to create an inclusive village. Originality: This study confirms the application of collaborative governance in realizing inclusive villages in Sidorejo.